Beartown eaudiobook - Backman, Fredrik (Beartown, 2017)
Now an HBO Original Series "You'll love this engrossing novel." — People Named a Best Book of the Year by LibraryReads , BookBrowse , and Goodreads From the #1 New York Times bestselling author of Anxious People, a dazzling and profound novel about a small town with a big dream—and the price required to make it come true. By the lake in Beartown is an old ice rink, and in that ice rink Kevin, Amat, Benji, and the rest of the town's junior ice hockey team are about to compete in the national semi-finals—and they actually have a shot at winning. All the hopes and dreams of this place now rest on the shoulders of a handful of teenage boys. Under that heavy burden, the match becomes the catalyst for a violent act that will leave a young girl traumatized and a town in turmoil. Accusations are made and, like ripples on a pond, they travel through all of Beartown. This is a story about a town and a game, but even more about loyalty, commitment, and the responsibilities of friendship; the people we disappoint even though we love them; and the decisions we make every day that come to define us. In this story of a small forest town, Fredrik Backman has found the entire world.